Farnesol delivery via polymeric nanoparticle carriers inhibits cariogenic cross-kingdom biofilms and prevents enamel demineralization - Ito, Tatsuro; Sims, Kenneth R.; Liu, Yuan; Xiang, Zhenting; Arthur, Rodrigo A.; Hara, Anderson T.; Koo, Hyun; Benoit, Danielle S. W.; Klein, Marlise I. [UNESP] (Wiley, 2022)
Streptococcus mutans and Candida albicans are frequently detected together in the plaque from patients with early childhood caries (ECC) and synergistically interact to form a cariogenic cross-kingdom biofilm. However, this biofilm is difficult to control. Thus, to achieve maximal efficacy within the complex biofilm microenvironment, nanoparticle carriers have shown increased interest in treating oral biofilms in recent years. Here, we assessed the anti-biofilm efficacy of farnesol (Far), a hydrophobic antibacterial drug and repressor of Candida filamentous forms, against cross-kingdom biofilms employing drug delivery via polymeric nanoparticle carriers (NPCs). We also evaluated the effect of the strategy on teeth enamel demineralization. The farnesol-loaded NPCs (NPC+Far) resulted in a 2-log CFU/mL reduction of S. mutans and C. albicans (hydroxyapatite disc biofilm model). High-resolution confocal images further confirmed a significant reduction in exopolysaccharides, smaller microcolonies of S. mutans, and no hyphal form of C. albicans after treatment with NPC+Far on human tooth enamel (HT) slabs, altering the biofilm 3D structure. Furthermore, NPC+Far treatment was highly effective in preventing enamel demineralization on HT, reducing lesion depth (79% reduction) and mineral loss (85% reduction) versus vehicle PBS-treated HT, while NPC or Far alone had no differences with the PBS. The drug delivery via polymeric NPCs has the potential for targeting bacterial-fungal biofilms associated with a prevalent and costly pediatric oral disease, such as ECC.
Keywords: cross-kingdom biofilm; demineralization; dental caries; farnesol; nanoparticle carriers